QUALITY OF LIFE AT WORK IN A PUBLIC MOTHER-CHILD CENTER IN SOUTHEASTERN BRAZIL - de Oliveira Lima, Lucas Alves; de Carvalho Fonseca, Elisama Angélica; Domingues, Paulo Lourenço; Peixoto, Karen Martins; da Silva, Caio Barros Gomes (International Journal of Research -GRANTHAALAYAH, 2020)
The general objective of this research was to analyze the perceptions of public employees of a Mother and Child Center in the municipality of Paraíba do Sul/RJ about what is Quality of Life at Work (QLW) and the main positive and negative factors that affect quality of life in the unit. This is an exploratory survey of qualitative approach, where techniques of observation and structured interview were used through a questionnaire answered by ten employees. Through the results, it was possible to verify that the main perceptions about QLW are linked to good interpersonal relationships and well-being in the service. Regarding the positive aspects of the work, good relationships with colleagues were highlighted, while the negative elements were the lack of materials to perform the tasks and the high workload.